SIFAT KIMIA ULTISOLS BANTEN AKIBAT PENGOLAHAN TANAH DAN PEMBERIAN PUPUK KOMPOS - Dewi Firnia (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2009)
ABSTRACTThe objective of this experiment were find out interaction effect between soil tillage and Compost dose to some chemistry properties of Ultisols Banten . The experiment was carried at the Kampung Baru Petir Serang Banten from June to September 2008, by using Randomized Block Design with factorial pattern and three replications. The first factor was soil tillage (one, two and three time tillage), and the second factor was compost dung (0; 10; 20; and ton ha-1). The data of experiment were analyzed by Fisher test and Duncan multiple range test =0,05 The result of experiment showed there was interaction effect between soil tillage and compost dosages only on the soil pH, but independently soil tillage and compost dosages application gave significant effect chemical properties ( C-Organic, and Nitrogen).Key words: Soil Tillage, Compost dung, Ultisols